Análisis de ejecución de la normativa de participación ciudadana en el año 2012, para la elaboración de la programación anual de la política pública y el presupuesto participativo en el Gobierno Autónomo Descentralizado de la Parroquia Rural San Lucas del cantón Loja - Escobar Cordero, Saara Felicia (2016)
In the present investigation an analysis of citizen participation takes place in the Decentralized Autonomous Government of San Lucas in 2012, it aims to determine the level of knowledge and implementation of the rules of citizen participation in Decentralized Autonomous Government members parish rural, to prepare the Annual Program of Public Policy and the Participatory budget. It is considered as rules of citizen study participation, the Ecuadorian Constitution establishes different levels of government, the Organic Code of Organization Territorial Autonomy and Decentralization that defines responsibilities and powers of the same, plus the Organic Law of Citizen Participation, the Organization Code Planning and Public Finance, and the Organic Law of the Council of Citizen Participation and Social Control. In addition the level of citizen participation in Decentralized Autonomous Government vestry San Lucas is determined, in developing the annual program of public policy and budget in 2012. Finally, the opportunities for citizen participation that promotes identified local government.